Climatic changes and distribution of plant formations in the state of Paraíba, Brazil - Cámara Artigas, Rafael; Israel de Souza, Bartolomeu; Porto de Lima, Raquel (Cuadernos de Investigación Geográfica, 2022)
The state of Paraíba in northeast Brazil contains four of the seven biomes present in the country: Mata Atlântica, Cerrado, Caatinga and Matas Serranas. On the other hand, Amazônia, Pantanal and Pampa were not found in this area. This special situation allows us to analyse changes in the distribution of these four large Brazilian biomes according to bioclimatic conditions, using the methodology of bioclimatic regime types. Based on the analysis of variables from periods of hydric and thermal vegetation stagnation, obtained from hydric and bioclimatic balances, average monthly temperature and rainfall, that methodology enables us to establish a typology of 27 types of bioclimatic regimes and 243 bioclimatic regime subtypes with the 9 Thornthwaite ombrothermal levels. In Paraíba 4 types of bioclimatic regimes are currently identified (mesophyllo, tropophyllo, xerophyllo and eurythermophilous) and 9 subtypes according to ombrothermal levels. In order to analyse the changes, extreme change situations were chosen: a past scenario with the Last Glacial Maximum (40 ky); and an RCP 8.5 climate change scenario for the CMSS 4.0 model for the year 2070. This enabled 3 bioclimatic regime maps of each of the 3 aforementioned situations to be obtained, providing a map of potential distribution of the plant formations of Paraíba state according to the specific field knowledge and bioclimatic mapping obtained for the present. This paper concludes that a retrocession of the Mata Atlântica can be seen from the Last Glacial Maximum up to the present, losing its optimal bioclimatic conditions and therefore remaining in a highly fragile relict situation in the face of anthropic pressure (sugarcane cultivation and urban expansion); an advance toward 2070 of the Caatinga in its shrub form as a predominant formation is indicated by the projection of climate change in 2070 for the analysed situation, specifically resulting from anthropic pressure, in this case due to livestock activities which have affected this biome in Paraíba since the mid-19th century.